Contemporary issues in north-south health research partnerships: perspectives of health research stakeholders in Zambia - Tulani Francis L. Matenga; Joseph Mumba Zulu; J. Hope Corbin; Oliver Mweemba (BMC, 2019)
Abstract Background The late 1990s and early 2000s have seen a growth in north-south health research partnerships resulting from scientific developments such as those in genetic studies and development of statistical techniques and technological requirements for the analysis of large datasets. Despite these efforts, there is inadequate information representing the voice of African researchers as stakeholders experiencing partnership arrangements, particularly in Zambia. Furthermore, very little attention has been paid to capturing the practice of guidelines within partnerships. In this paper, we present achievements and highlight challenges faced by southern partners in north-south health research partnerships. Methods A qualitative inquiry was employed using in-depth interviews developed using the Bergen Model of Collaborative Functioning with 20 key informants in Lusaka district in Zambia purposively sampled from a wide range of health research partnerships. Results Partnerships produce benefits for southern partners, including evidence generation to influence policy, improved service delivery, infrastructure development and designing interventions to improve the healthcare of populations in greatest need. Most importantly, through partnerships, there is availability of financial resources to accomplish partnership goals. For success to be achieved, there must be effective communication and leadership, values and accountability that go into the process of partnership functioning. Trust interacts with different elements that create partnerships where there is co-ownership of study rewards. Challenging aspects of the interaction are largely due to funding mechanisms where 90% of the funding for health research is from northern partners. This funding mechanism results in power imbalances that lead to publication challenges, dictation of research agenda and ownership of samples and data leading to a general lack of motivation to collaborate. Conclusion Mistrust has implications on joint working such that partners find it difficult to work together and produce results greater than their individual efforts. Property rights and resource sharing must be resolved early in the partnership and each partner's contributions recognised. These findings highlight areas that partnerships need to focus on to make the most of guidelines on research partnership with developing countries.